Current status and perspectives of hematopoietic cell transplantation in patients with paroxysmal nocturnal hemoglobinuria - Marek Ussowicz; Dawid Przystupski; Patrycja Mensah-Glanowska; Agnieszka Piekarska (Frontiers in Immunology)
BackgroundParoxysmal nocturnal hemoglobinuria (PNH) is a rare complement-driven acquired hemolytic anemia with specific presentations of hemoglobinuria, abdominal pain, fatigue, and thrombosis.ObjectiveTo review the current therapeutic strategies for PNH, including anti-complement therapy and allogeneic hematopoietic cell transplantation (alloHCT), focusing on the tailoring of the approach to the disease subtype.ResultsThe outcome of alloHCT varies depending on disease severity, thrombotic history, and response to prior therapies. Non-transplant PNH therapies include anti-C5 monoclonal antibodies that reduce terminal complement activation (eculizumab, ravulizumab, and crovalimab) and proximal complement pathway inhibitors such as pegcetacoplan (C3 inhibitor), iptacopan (complement factor B inhibitor), and danicopan (complement factor D inhibitor). Although complement inhibitors have revolutionized treatment, alloHCT remains the only curative therapy, particularly for patients who are refractory to medical management or have severe cytopenia. This review outlines the conditioning regimens used in alloHCT and summarizes recent studies showing that overall survival rates improve with less toxic conditioning protocols.ConclusionsAlloHCT can be used to manage PNH, particularly in patients who are resistant to or without access to complement-targeted therapies. Any potential cure offered by alloHCT must be counterbalanced by the significant procedure risks, including graft-versus-host disease and transplant-related mortality, particularly in patients with comorbidities. In the case of severe aplastic anemia with an associated PNH clone, immunoablative protocols based on anti-thymocyte globulin serotherapy with fludarabine and cyclophosphamide are recommended. The use of reduced toxicity protocols with fludarabine has been well-documented in patients with classic PNH. A treosulfan/fludarabine-based regimen is recommended; however, there is no consensus on optimal drug selection.